Slaughterhouse-five or The children's crusade : a duty-dance with death - Vonnegut, Kurt. (New York : Dial Press, 2009)
Billy Pilgrim returns home from the Second World War only to be kidnapped by aliens from the planet Tralfamadore, who teach him that time is an eternal present.
Originally published by Delacorte Press in 1969.
"Dial Press Trade Paperback Edition" -- t.p. verso.
Keywords: World War, 1939-1945 -- Fiction; Free will and determinism -- Fiction; English literature; Free will and determinism; Historical fiction; Science fiction; War stories; War stories; Fiction; War stories